WOMEN EMPOWERMENT THROUGH SONG LYRICS: FEMINISM PERSPECTIVES OF KATY PERRY’S ROAR - Neisya Neisya; Fitria Aprilia; Adilla Nadya Soraya Darlius; Fani Lestiana (University of Kuningan, 2023)
Song can be used as a medium of expression because it expel feelings and thoughts as well as a medium of entertainment. Song lyrics created by composers often use distinctive language to create aesthetic effects, such as figurative language and imagery. Unfortunately, the use of it often makes listeners not fully aware of the song meaning and not feeling the emotions that are actually intended to be conveyed. This study aims to reveal the meanings and messages implied in the lyrics of Katy Perry's song Roar through an analysis of figurative language and imagery from a feminism perspective. The method used is descriptive qualitative through the process of data reduction, data presentation, and the last is drawing conclusions. The results showed that there were 7 types of figurative language; simile, metaphor, personification, synecdoche, symbol, paradox, and hyperbole. In addition, Katy also uses 4 types of imagery; visual imagery, auditory imagery, organic imagery, and kinesthetic imagery. All the figurative language and imagery represent Katy's feelings and struggles against the downturn during her relationship with her ex-lover and managed to get up hence she can love herself. This is the message that Katy wants to convey to all women in the world that they are precious beings who have choices in their lives and are able to stand alone without any help from men.Keywords: feminism; figurative language; imagery; Roar song; women empowerment.